2020
DOI: 10.5455/medarh.2020.74.298-304
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Needs of Adolescents Assessed During the Years of Global Financial Crisis: a Systematic Review

Abstract: Introduction: Mental health issues during adolescence are common and worsen when financial crisis occur across the world. Identification of mental health needs as they are expressed by adolescents themselves is important for efficient mental health promotion interventions. Aim: This systematic review examined studies on the mental health needs among adolescents from their own perspective. Methods: Four databases were searched between 2008-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(72 reference statements)
0
4
2
Order By: Relevance
“…Secondly, anxiety exhibited a positive association with resilience and daily allowance, which contrasts with previous studies indicating an inverse relationship between anxiety and resilience [40,41]. Additionally, our ndings diverge from other research linking nancial hardship to poor mental health among adolescents [42,43]. This inconsistency may be attributed to variances in measurement methodologies or other factors, such as distinct parenting styles, the quality of parent-child attachment, prior mental health experiences, or peer in uences [43][44][45][46][47].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Secondly, anxiety exhibited a positive association with resilience and daily allowance, which contrasts with previous studies indicating an inverse relationship between anxiety and resilience [40,41]. Additionally, our ndings diverge from other research linking nancial hardship to poor mental health among adolescents [42,43]. This inconsistency may be attributed to variances in measurement methodologies or other factors, such as distinct parenting styles, the quality of parent-child attachment, prior mental health experiences, or peer in uences [43][44][45][46][47].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, our ndings diverge from other research linking nancial hardship to poor mental health among adolescents [42,43]. This inconsistency may be attributed to variances in measurement methodologies or other factors, such as distinct parenting styles, the quality of parent-child attachment, prior mental health experiences, or peer in uences [43][44][45][46][47].…”
Section: Discussioncontrasting
confidence: 90%
“…As mental health problems in adolescents have been a common public health issue [ 3 , 38 ], regular and simple screening tools for specific mental health problems, such as depression and anxiety disorders, are becoming increasingly needed. In this study, we gained convincing evidence that the GAD-7 is a reliable and valid self-reported measure with good psychometric properties in Chinese adolescents aged 10 to 17 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we found that 40% of the adolescents worried about climate change [ 44 ], which might be an indicator that worry in general and negative thoughts about the future go hand in hand. Another explanation for worries in adolescents in recent years might be the unstable socio-economic situation following the global financial crisis of 2008 [ 45 ]. However, the unemployment rate in Norway is among the lowest in the world [ 46 ], and the financial crisis does not seem to have had a major impact on the mental health of the Norwegian population in general [ 47 ].…”
Section: Discussionmentioning
confidence: 99%